2021
DOI: 10.1038/s41598-020-80234-z
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial shape in patients with beta thalassaemia: a geometric morphometric analysis

Abstract: The shape of the craniofacial complex of patients with beta thalassaemia was evaluated using geometric morphometrics on lateral cephalometric radiographs and was compared with matched controls. The beta thalassaemia group consisted of 40 patients (16 females, 24 males, mean age 33.4). Each patient was matched by age and gender to two controls (32 females, 48 males, mean age 33.1). The 120 lateral cephalometric radiographs were digitized and traced with 15 curves, 10 landmarks and 117 sliding semi-landmarks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Reduced posterior facial height is attributed to anemia which results in growth retardation at the condylar region. 11 Our patient exhibited increased gingival display due to short lip as well as vertical maxillary excess and also high articular angle (=156°), which affected the vertical dimension and was exhibited by an increase in the vertical cephalometric parameters (Go-Gn to SN=46°, FMA=35°) and reduction in posterior facial height (PFH/AFH=55.77%). The above findings and considering age of the patient, it was decided to start with interceptive treatment by giving a high pull headgear to restrain the maxilla and prevent further vertical growth.…”
Section: Discussionmentioning
confidence: 71%
“…Reduced posterior facial height is attributed to anemia which results in growth retardation at the condylar region. 11 Our patient exhibited increased gingival display due to short lip as well as vertical maxillary excess and also high articular angle (=156°), which affected the vertical dimension and was exhibited by an increase in the vertical cephalometric parameters (Go-Gn to SN=46°, FMA=35°) and reduction in posterior facial height (PFH/AFH=55.77%). The above findings and considering age of the patient, it was decided to start with interceptive treatment by giving a high pull headgear to restrain the maxilla and prevent further vertical growth.…”
Section: Discussionmentioning
confidence: 71%
“… 17 , 18 Furthermore, the photographic parameter measurements in the IT group, although different from those of the control group, showed a smaller mean difference than observed in the BT group, thereby suggesting that induction therapy might have decreased extra-medullary hematopoiesis by increasing hemoglobin production, as suggested in the literature. 19 Interestingly, post hoc analysis revealed that the IT and BT groups did not differ significantly in upper face, nasal, and forehead heights, possibly because of the relatively small sample size or the duration of therapy in the IT group. A prior study has reported shorter upper facial height and lower facial height in patients with thalassemia receiving blood transfusion than control participants, thus suggesting a differential delay in the development of the facial skeleton in individuals with thalassemia.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, GM has been used to study the pattern of sutural closure and the resulting bony growth in patients with craniosynostosis 36-38 -as well as the shape variability of the cranial base, the maxilla, and the mandible of patients with beta thalassaemia based on principal components analysis. 39 Moreover, applying partial least square analysis on subjects with achondroplasia allowed to identify a signi cant axis of covariation between shape and age. These results enabled to predict during the growth the increase of morphological differences on ve anatomical regions located on the skull and the mandible.…”
Section: Discussionmentioning
confidence: 99%